Multilingual practices and ideologies of refugees in the Neoliberal Era: the case of North Korean refugee students in South Korea. Issue 4 (1st October 2016) - Lee, Mun Woo; Han, Moon-sub; Hyun, Eun Ryung
ABSTRACT: This study investigates the multilingual practices and ideologies of North Korean refugee students in neoliberal South Korean society. Language tracking forms were completed over a seven-day period and individual interviews about participants' perceptions of English, Chinese, South Korean, and North Korean were conducted. The findings show that the students perceived English as the most powerful language despite its restricted usage. The students used South Korean most of the time, reflecting its socially favoured status. In contrast, North Korean was an inner-circle language, and its use also negatively influenced perceptions of spoken Chinese. The participants devalued their Chinese language ability because the combination of North Korean and Chinese was not as socially favourable as other language combinations. This study reveals how an underrepresented population's language practices are intertwined with the power relations of macro-level social structures through the complex interrelationship among the aforementioned languages in the neoliberal South Korean context.